Beric the Briton (unabridged) - Weiss, Jim; Henty, G. A. (Greathall Productions Inc., 2005)
Tells the story of a young man, Beric, who lived during the time of the Roman invasion of Britain.
Keywords: Great Britian -- Juvenile Fiction -- Audio book -- History -- Roman Period -- 55 BC- 499 AD